2012
DOI: 10.1175/jas-d-11-0257.1
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of the Self-Aggregation of Convection in Cloud-Resolving Simulations

Abstract: In models of radiative-convective equilibrium it is known that convection can spontaneously aggregate into one single localized moist region if the domain is large enough. The large changes in the mean climate state and radiative fluxes accompanying this self-aggregation raise questions as to what simulations at lower resolutions with parameterized convection, in similar homogeneous geometries, should be expected to produce to be considered successful in mimicking a cloud-resolving model.The authors investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
613
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(676 citation statements)
references
References 25 publications
55
613
8
Order By: Relevance
“…Figure 1 shows x-y snapshots of specific humidity q on day 60 at z = 500 m for various domain sizes L. Aggregation, with its trademark dry patches in regions of steady-state subsidence, is clearly evident for domain sizes larger than L 300 km. This is in rough agreement with the critical domain size of 200-300 km found in Bretherton et al [2005] and Muller and Held [2012].…”
Section: Aggregation In 3-dsupporting
confidence: 90%
See 3 more Smart Citations
“…Figure 1 shows x-y snapshots of specific humidity q on day 60 at z = 500 m for various domain sizes L. Aggregation, with its trademark dry patches in regions of steady-state subsidence, is clearly evident for domain sizes larger than L 300 km. This is in rough agreement with the critical domain size of 200-300 km found in Bretherton et al [2005] and Muller and Held [2012].…”
Section: Aggregation In 3-dsupporting
confidence: 90%
“…The initial temperature profile was obtained from a small-domain (i.e., non-aggregated) simulation of radiative-convective equilibrium. We turned off large-scale dynamical forcings, set initial horizontal winds to zero, and nudged the horizontal-mean winds to zero over a time scale of two hours, both for consistency with previous work [Muller and Held, 2012;Bretherton et al, 2005] and because we found these adjustments conducive to aggregation.…”
Section: Numerical Simulationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Specific limitations of modeled clouds include both features which differ from what one observes (e.g., ''too few, too bright,'' [Webb et al, 2001;Nam et al, 2012]) as well as features which are inadequately understood (e.g., controls on cloud vertical structure [Nuijens et al, 2015], and organization [Bretherton et al, 2005;Muller and Held, 2012;Wing and Emanuel, 2014]). An important component of these limitations is the delicacy of the interactions between clouds and circulations Sherwood et al, 2014].…”
Section: Introductionmentioning
confidence: 99%